Spread of quarantine weeds in Ukraine - Holiachuk, Yu.; Kosylovych , H. (Quarantine and plant protection, 2025)
Goal. To analyze the dynamics and distribution range of quarantine weed species in Ukraine (excluding territories affected by active or past hostilities and those temporarily occupied by the Russian Federation) over the past ten years. Methods. Interpretation of official data from the State Service of Ukraine on Food Safety and Consumer Protection regarding the spread of quarantine weeds using an analytical-comparative method. Results. Between 2015 and 2024, outbreaks of nine weed species and one genus with the status of limited distribution were recorded in Ukraine. The largest infested areas are occupied by common ragweed (Ambrosia artemisiifolia), which has been reported in all regions of the country. Significant infestations of creeping knotweed (Polygonum convolvulus) were also recorded in five southern and eastern regions. In 2024, beaked nightshade (Solanum rostratum) was detected in one region, Aleppo millet grass (Sorghum halepense) in two, and long-spine sandbur (Cenchrus longispinus) in five southern regions and the Kyiv region. Within the genus Cuscuta, the spread of field dodder (Cuscuta campestris), Lehmann’s dodder (Cuscuta lehmanniana), Mediterranean tree dodder (Cuscuta epithymum), and hop dodder (Cuscuta lupuliformis) has been observed, with field dodder being the most prevalent. Since 2019, hop dodder has been officially recorded in Ukraine, and since 2021, the spread of Cuscuta spp. has been noted. As of 2024, Cuscuta spp. were registered in three regions. Over the past decade, there has been a general trend of decreasing areas infested with quarantine weed species, with the exception of Cuscuta species, particularly Lehmann’s dodder. The infested area of beaked nightshade has remained unchanged. Conclusions. The development and spread of quarantine weeds pose a serious threat to the national economy, particularly the agricultural sector, as well as to human and animal health. In order to prevent the introduction and spread of quarantine weed species across the country, business entities involved in the cultivation, handling, or trade of plants and plant products must strictly adhere to plant quarantine legislation.